The Cytotoxic Activity of Solanum Nigrum Ethanolic Extract on Widr Human Colon Cancer Cells - Maruti, Astrid Ayu; F, Ilham Augusta; Putri, Dyaningtyas D.P.; Hermawan, Adam; Ikawati, Muthiâ (Indonesian Journal of Cancer Chemoprevention, 2011)
Solanum  nigrum  L.  or  Leunca  in  Indonesia  has  been  traditionally  used  as  a  herbal plant,  which  is  believed  to  have  anti-tumor  properties,  although  the  mechanism  for  the activity  remains  unknown.  The  resecarch  aim  to  examine  the  cytotoxic  effect  of  the ethanolic extract of Solanum nigrum on WiDr human colon cancer cells. In this study, we prepared an ethanol extract from herb of Solanum nigrum and investigated the mechanism involved  in  its  growth-inhibitory  effect  on  WiDr  human  colon  cancer  cells.  Herbs  of Solanum nigrum dry powder is extracted with 70% ethanol then added into the WiDr cell culture  in  96  wells  plate  in  various  concentration  :  50,  100,  250,  and  500  µg/ml. Cytotoxicity  of  the  Solanum  nigrum  ethanolic  extract    was  analyzed  with  MTT  assay  on WiDr human colon cancer cell lines. Results from the MTT assay showed WiDr cells was weakly  suppressed  in  the  presence of  the  extract.  The  result  of  the  assay  also  showed a very  close  correlation  between  the  Solanum  nigrum  extract  concentration  and  the surviving  cell  numbers  which  means  the  extract  caused  cell  death  in  a  dose-dependent fashion  in  WiDr  cancer  cells  with  the  IC50  of  359,23  µg/ml.  Collectively,  the  research suggest  further  studies  to  explore  other  chemopreventive possibilites  of  Solanum  nigrum ethanolic extract.Key words : colon cancer, MTT assay, cytotoxic, WiDr, Solanum nigrum